INTRODUCTION TO STRUCTURAL EQUATION MODELLING USING SPSS AND AMOS - Y. Mehlsen, Mimi (Psyke & Logos, 2009)
En anmeldelse af: Niels J. Blunch Introduction to Structural Equation Modelling using SPSS and AMOS